One-pot, multicomponent synthesis of 2, 3-disubstituted quinazolin-ones with potent and selective activity against Toxoplasma gondii. Issue 9 (15th May 2018) - Brown, Carla E.; Kong, Tiffany; Bordón, Claudia; Yolken, Robert; Jones-Brando, Lorraine; McNulty, James
Graphical abstract: Abstract: The discovery of two quinazolinones with selective, single-digit micromolar activity (IC50  = 6–7 µM) against the tachyzoites of the apicomplexan parasite Toxoplasma gondii is reported. These potent and selective third generation derivatives contain a benzyloxybenzyl substituent at C 2 and a bulky aliphatic moiety at N3. Here we show that these quinazolinones inhibit T. gondii tachyzoite replication in an established infection, but do not significantly affect host cell invasion by the tachyzoites.